Impact of polyvinyl chloride nano-plastics on the biochemical status of Oreochromis niloticus under a predicted global warming scenario - Ahmed Mohamed Soliman; Ayman S. Mohamed; Amr A. Abdel-Khalek; Shereen R. Badran (Scientific Reports)
Abstract Plastic pollution and global warming are widespread issues that lead to several impacts on aquatic organisms. Despite harmful studies on both subjects, there are few studies on how temperature increases plastics’ adverse effects on aquatic animals, mainly freshwater species. So, this study aims to clarify the potential impact of temperature increases on the toxicological properties of polyvinyl chloride nano-plastics (PVC-NPs) in Nile tilapia (Oreochromis niloticus) by measuring biochemical and oxidative biomarkers. The fish groups were subjected to three distinct temperatures (30, 32, and 34 °C) and subsequently separated into two groups: 0 and 10 mg/L of PVC-NPs, as it is expected that these temperatures may modify their chemical properties, which can influence their absorption and toxicity in fish. After 4 days, the biochemical response of fish exposed to PVC-NPs and elevated temperatures showed a significant increase in the levels of plasma total proteins, albumin, globulin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), creatinine, and uric acid. Additionally, the level of oxidative stress biomarkers in the liver, gills, and brain was found to have a significant increase in malondialdehyde (MDA) concentration and a decrease in glutathione reduced (GSH) concentration and catalase (CAT) activity in all studied groups. Finally, the current findings revealed a synergistic cytotoxic effect of PVC-NPs and temperatures on the metabolic and oxidative stress indices of O. niloticus.